(untitled) (Eurasian Scientific Herald, 2023)
The main source after the Qur’an Karim covering the foundations of the teaching of Islam is Hadith. Collecting Hadiths and giving them a certain order began mainly from the second half of the 8th century, when it was ordered by the most knowledgeable, someone with great life experience (muhaddis)who perfectly learned the basics of various sciences. In the 8th-11th centuries, more than four hundred muhaddis were involved in the science of Hadith. This is a specific area of study of knowledge and was carried out under the name "science of Hadith". In the following years, hadiths containing the life, work of Muhammad Salam and his religious and moral instructions, Imam Ismail alBukhari’s "Al-jome’ as-sahih" ("the convincing collection"), "Al-adab al-mufrad" ("the Adab masterpieces"), Imam Isa Muhammad ibn Isa at-Termizi’s "Ash-Shamoil annabawiya" were published. The words” hadith “or” Sunna", meaning one, consist of narratives about the life and work of the Messenger and his religious and moral instructions.The main source after the Qur’an Karim covering the foundations of the teaching of Islam is Hadith